2009
DOI: 10.1152/ajpgi.90708.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the artificial sweetener, sucralose, on gastric emptying and incretin hormone release in healthy subjects

Abstract: . Effect of the artificial sweetener, sucralose, on gastric emptying and incretin hormone release in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
165
4
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(192 citation statements)
references
References 48 publications
17
165
4
6
Order By: Relevance
“…Our data are in accord with recently published human data (Ma et al, 2009) and in vivo rat data (Fujita et al, 2009), in which sucralose ingestion failed to stimulate a rise in two circulating incretin hormones, GLP-1 and the K cell-derived glucose-dependent insulinotropic polypeptide. Ma et al administered sucralose nasogastrically to healthy, normalweight volunteers and observed no effect on plasma GLP-1 or glucose-dependent insulinotropic polypeptide concentrations (Ma et al, 2009). Similarly, Fujita et al demonstrated in rats that in contrast to sucrose gavage, oral gavage of sucralose did not induce a rise in plasma GLP-1 (Fujita et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data are in accord with recently published human data (Ma et al, 2009) and in vivo rat data (Fujita et al, 2009), in which sucralose ingestion failed to stimulate a rise in two circulating incretin hormones, GLP-1 and the K cell-derived glucose-dependent insulinotropic polypeptide. Ma et al administered sucralose nasogastrically to healthy, normalweight volunteers and observed no effect on plasma GLP-1 or glucose-dependent insulinotropic polypeptide concentrations (Ma et al, 2009). Similarly, Fujita et al demonstrated in rats that in contrast to sucrose gavage, oral gavage of sucralose did not induce a rise in plasma GLP-1 (Fujita et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous human studies in which no effect on plasma glucose and insulin was observed following ingestion of encapsulated sucralose in diabetic patients (Grotz et al, 2003) or following intragastric infusion of sucralose in healthy subjects (Ma et al, 2009). Similarly, oral gavage of sucralose in rats did not improve glucose homeostasis following an intraperitoneal glucose-tolerance test (Fujita et al, 2009), suggesting that there was no incretin effect mediated by the sucralose gavage.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More recently, a mechanism involving activation of the sweet taste-receptor, gustducin, has also been proposed [33]. However, it is still unclear whether all of the above mentioned pathways are involved in mediating glucose-induced incretin hormone secretion in humans, since neither sulphonylureas nor ingestion of non-calorific non-metabolizable sweeteners have been observed to affect incretin levels in clinical studies [34][35][36]. It has been thought that glucose was able to stimulate GLP-1 secretion only via interaction with the apical (luminal) membrane of the L-cell, as intravenously infused glucose was not thought to result in elevated GLP-1 levels.…”
Section: Direct Luminal Stimulation Of Enteroendocrine Cellsmentioning
confidence: 99%
“…However, we recently demonstrated that sucralose, in two different loads, had no effect on GLP-1, glucose-dependent insulinotrophic polypeptide or insulin secretion, and that it did not elicit any feedback response on gastric emptying in healthy human subjects (5) . While this implies that artificial sweeteners may have no therapeutic benefit in the dietary management of diabetes, other than as a substitute for carbohydrates, it remains possible that sucralose affects small intestinal carbohydrate absorption as a result of its interaction with the sweet taste receptors.…”
mentioning
confidence: 91%